The Importance of Tubular Function in Chronic Kidney Disease (2019)
Glomerular filtration rate (GFR) and proteinuria-albuminuria are the renal functional parameters currently used to evaluate chronic kidney disease (CKD) severity. However, tubular secretion is another important renal functional parameter to be taken into account since proximal tubule (PT) secretion, in particular, is a crucial renal mechanism for endogenous organic cations, anions and drug elimination. The residual diuresis is a relevant survival predictor in patients on dialysis, since their urine is produced by the glomerular and tubular functions. It has been hypothesized that drugs which up-regulate some renal tubular transporters could contribute to uremic toxin excretion, and nephroprevention. However, if tubular transporters' down-regulation observed in CKD patients and experimental models is a PT adaptation to avoid intracellular accumulation and damage from uremic toxins, consequently the increase of toxin removal by inducing tubular transporters' up-regulation could be deleterious to the kidney. Therefore, a deeper understanding of this phenomenon is currently needed. In conclusion, tubular function has an important role for endogenous organic cations, anions and drug excretion in CKD patients, and a deeper understanding of its multiple mechanisms could provide new therapeutic alternatives in this population.